Entrapment of Volvariella Volvacea Spores in Electrospun Nanofibers - Azaddin, Aiman Farhana; A. Rahman, Roshanida; Md Illias, Rosli; Jusoh, Mazura; Jaafar, Juhana (Journal of Sustainable Natural Resources, 2020)
Nanofibers containing Volariella volvacea spores was prepared by electrospinning technique. It has been one of the promising and alternative techniques in immobilizing microorganism cells including bacteria, virus and fungi through entrapment process. The nanosize electrospun nanofibers exhibit outstanding properties including high porosity and reusability which make them an ideal candidates for various types of potential application especially in bioprocess development. In the present study, the spores of Volvariella volvacea was suspended in a series of polymer solutions (poly (vinyl alcohol) and polyvinyl pyrrolidone) and subjected to an electrostatic field supplied by the power voltage. The viability of the entrapped spores was estimated through microorganism cells test by culturing the obtained nanofiber mats on potato dextrose agar (PDA) and studying their growth rate. The Volvariella volvacea spores electrospun in nanofibers remained viable for 12 days at room temperature (30ËšC) with PVP electrospun nanofiber chosen as the best carrier matrix for entrapment of Volvariella volvacea. The present result demonstrated that electrospinning process possess high potential in entrapping and immobilizing of microorganism cells.